2015
DOI: 10.1093/cvr/cvv121
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 protects the mouse heart from ischaemic injury by regulating cell death

Abstract: These findings reveal a pivotal role for miR-150 as a regulator of cardiomyocyte survival during cardiac injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 59 publications
8
121
1
3
Order By: Relevance
“…In this study, we demonstrated for the first time that miR-150 suppresses cardiac fibrosis via c-Myb. Tang Y et al previously reported that miR-150 could repress the ischemia-induced apoptosis of cardiomyocytes by repressing the proapoptotic genes ERG2 (zinc-binding transcription factor induced by ischemia) and P2X7R (pro-inflammatory ATP receptor) [54]. The underlying mechanisms of cardiac fibrosis in different diseases are different, but there are some commonalities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated for the first time that miR-150 suppresses cardiac fibrosis via c-Myb. Tang Y et al previously reported that miR-150 could repress the ischemia-induced apoptosis of cardiomyocytes by repressing the proapoptotic genes ERG2 (zinc-binding transcription factor induced by ischemia) and P2X7R (pro-inflammatory ATP receptor) [54]. The underlying mechanisms of cardiac fibrosis in different diseases are different, but there are some commonalities.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction was induced by permanent left-anterior descending coronary artery ligation as previously described [12, 13]. Briefly, mice were anaesthetized by using pentobarbital sodium (50 mg/kg, P3761, Sigma-Aldrich, St Louis, MO, USA) by intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%
“…Formation of a nuclear complex of β-arrestin1 with the heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) and Drosha, which are crucial nuclear RNA-binding proteins involved in miR processing (Lee et al ., 2003; Guil and Caceres, 2007), leads to activation of RNA helicase-independent miR processing (Kim et al ., 2014). In the mouse hearts, 7-day carvedilol infusion induced the upregulation of miR-150, miR-214, miR-125b-5p and miR-199a-3p, which were shown to be cardioprotective in the mouse models of heart failure (Salloum et al ., 2010; Aurora et al ., 2012; Wang et al ., 2014; Tang et al ., 2015). Moreover, our group also showed that 7-day infusion of carvedilol induced a unique gene signature on multiple genes related to cardiac disease.…”
Section: Biased Signaling On Selected Gpcrsmentioning
confidence: 99%